An international award-winning photograph illustrates how graphics convey climate change communication messages - Deborah HILTON (Journal of Health and Social Sciences)
Climate change effects are becoming extreme, persistent and permanent, with negative ramifications on agriculture, more extreme weather catastrophes, detrimental effects on human physical and mental health, destruction of small islands and while economic impacts are difficult to estimate overall the situation is apocalyptic. Policy action should address urgent issues, and consistency requires climate change under- standing including knowledge of the human and environmental connections. Research showed that mass communication could be an important means to address environmental global warming. This paper shows that photographs can convey climate change communication messages. Public health committees and po- licymakers should utilise graphics on policy documents, websites and flyers to have dramatic influence over public opinion, to stimulate understanding and collective action.